The Determinant Mother Feeding on Children under Five Stunting Health Center in Rural Area - Ummah, Arief Khoerul (Jurnal Keperawatan Soedirman, 2024)
Stunting is a significant nutritional issue affecting children that has been the world's concern in recent years, especially in developing countries. The study aims to identify the determinant factors affecting mothers’ feeding practices for children experiencing stunting. The research used an observational and correlation design involving 258 respondents from three health centers. Data were collected through a questionnaire conducted between December 2022 and January 2023. The data analyzed utilized chi-square tests and logistic regression. The variables that dominantly contribute to the practice of meal provision included economic factors for children under five with stunting (P = 0.001, OR = 4.276), compared to other variables such as knowledge (P = 0.004, OR = 2.632), attitude (P = 0.001, OR = 3.237), hygiene (P = 0.013, OR = 3.552), and cultural factors (P = 0.001, OR = 3.216). Economic factors emerged as the primary determinants influencing meal provision practices for stunted toddlers. Economic factors were also dominantly associated with maternal feeding practices for stunted children under five in rural areas